Low-complexity signal detection algorithm for the power splitting receiver scheme - WANG Yanyan; LI Qidi; TANG Xiaohu (Tongxin xuebao)
To address the issue of high signal detection complexity in mobile communication systems based on the splitting receiver architecture, a low-complexity signal detection algorithm was proposed. Firstly, considering the influence of antenna noise, post-processing noises, and power splitting factor, a splitting receiver architecture was designed, and a simplified two-dimensional received signal model was further established. Then, by characterizing the joint probability density function of the two-dimensional received signal in the transformed coordinate system, a low complexity signal detection algorithm based on the minimum distance was achieved. Finally, compared to the conventional coherent receiver, the joint processing gain of the splitting receiver scheme was analyzed. Theoretical analysis demonstrates that the proposed signal detection algorithm has lower computational complexity compared to the traditional signal detection schemes based on three-dimensional received signals. Simulation results show that the approximation SER achieved by the low-complexity signal detection is very close to that of the accurate SER at a certain power splitting ratio. Also, the splitting receiver can achieve an improved SER performance compared to the conventional coherent receiver.